Exploring the option of student-run free health clinics to support people living with type 2 diabetes mellitus: a scoping review - Kovanur Sampath, Kesava; Ann-Rong, Yan; Haggie, Marrin; Tapara, Timi; Brownie, Sharon (Frontiers in Public Health, 2023)
Diabetes is a major cause of morbidity and premature mortality worldwide and now identified as a ‘public health emergency’ and a ‘modern and preventable pandemic’. Indigenous populations are disproportionately affected by type 2 diabetes mellitus (T2DM) and associated complications. Student run free clinics (SRFCs) may play an important role in the prevention and management of T2DM. The primary objective of this scoping review was to investigate the opportunity for curriculum enhancement through the role and effectiveness of SRFCs in managing T2DM. Electronic databases such as PubMed, CINAHL, Science Direct and Cochrane Library were searched from inception to October 2022. Identified records from database literature searches were imported into Covidence®. Two independent reviewers screened and extracted the data. The research team collectively created a data charting table/form to standardize data collection. A narrative synthesis was used to summarize the evidence. Six studies (total of 319 participants) that met our eligibility criteria were included in this scoping review. SRFCs can provide high-quality diabetic care, especially for uninsured and economically weaker population. Preliminary evidence further indicate that shared medical appointments and telehealth may facilitate diabetic care especially during times where access to care may be difficult (e.g., COVID lockdown). However, no study included in the review explored or discussed family centred/culturally sensitive interventions. Hence, such interventions should be made part of the curriculum in the future with students in SRFCs exposed to such an approach.